Ancient psychotechnics as a means of compensation of lost existential experience - Leonid Solonko (Cхід)
The present article deals with ancient psychotechnics and its role in restoring the access to existential experience that serves as a source of energy and basic vital intuition. The purpose is to determine the influence of psychotechnic traditions on compensation of deficiency of existential experience and unity of humans and the natural world in order to discover universal images and symbols which underlie all religious systems. Deep attention is paid to altered states of consciousness whose crucial importance reveals itself in the activation of subconscious mind and liberation from limitations imposed by the loss of connection with the Being in its simple and genuine forms. The author focuses on the description of common features that characterize religious systems regardless of cultural distinctions. It’s extremely significant to emphasize that those intuitions, considered as an inherent element of specific religion, are completely accessible to persons who belong to different cultural traditions. There are reasons to affirm that shamanism, Greek mysteries; Daoism, Hinduism and Buddhism have the same origin and the same mission - overcome alienation from the Being with the objective of achieving of personal salvation. Trance immersion deserves special mention because of the possibility of facilitating access to subconscious layers and transpersonal experiences as a means of reaching inner harmony. It is proved that the visions which arise in a trance state are nearly identical to hallucinations caused by psychotropic substances. Scientific innovation of the study consists in the attempt to demonstrate the correlation between ancient psychotechnic traditions and the urgent necessity to solve modern existential crisis.